Comparison of ultrasound and MRI shows equivalent accuracy and reliability in acromial index measurement - Schamberger, Christian T.; Großner, Tobias; Fischer, Christian; Findeisen, Sebastian; Ferbert, Thomas; Böpple, Jessica C.; Höppchen, Arnold; Schmidmaier, Gerhard; Stein, Stephan (Scientific reports, 2025)
The acromial index, a radiological parameter assessing the subacromial space, is vital for diagnosing conditions like rotator cuff tears and subacromial impingement syndrome as the acromial Index influences the choice of therapy. Traditionally determined via X-ray, AI is increasingly assessed using MRI due to its superior image quality. However, MRI’s cost and limited availability highlight the need for alternative methods. Ultrasound offers a promising, cost-effective alternative, providing real-time imaging without radiation exposure. This study aims to compare the accuracy and reliability of ultrasound-based AI determination with MRI. This retrospective study enrolled patients with shoulder complaints who underwent both MRI and ultrasound examinations between November 2021 and October 2022. Inclusion criteria included appropriate MRI and ultrasound images of the shoulder joint. AI was measured on MRI images and a modified AI was assessed using ultrasound. Statistical analyses evaluated the accuracy and reliability of both methods, focusing on intra- and interobserver consistency. A total of 113 patients (53.2 years average age, 31.3% female) were included. The mean MRI-determined AI was 0.65 (SD 0.065), with 15.6% showing pathological AI. Ultrasound-determined modified acromial index averaged 0.74 (SD 0.122), with 33% showing pathological modified acromial index. Comparative analysis showed no significant difference between MRI and ultrasound measurements (p = 0.237). Both methods demonstrated high intra- and interobserver reliability (ICC values > 0.9). Ultrasound-assisted AI determination is a valid, reproducible, and reliable alternative to MRI. Its advantages include cost-effectiveness, accessibility, and absence of ionizing radiation, making it particularly useful in resource-limited settings.